Did We Deliver Quality Education in Online Sessions During Covid 19 Lock Down? Learner’s Perspective from a Developing Country - Saman Malik, Faiqa Hassan, Shafaq Malik, Fatima Rizwan, Rizwan Sultan, Muhammad Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: COVID-19 pandemic pushed unprepared educational institutes towards online sessions. Though equivalence of online sessions proved already in many studies before pandemic, unplanned sessions and inexperienced teachers with networking issues and novice software for online sessions could not meet the standard of teaching that was expected or experienced during these sessions. We planned this study to know perspective of learners to measure quality of online sessions and to find out factors which could improve these sessions in future. Design: Prospective questionnaire based study Place & duration of study: Hitec IMS Dental College, from 10th Feb 2022 to 10th March 2022 Methodology: Questionnaire was distributed to 150 students of BDS who has attended online session during COVID-19 pandemic. Results: 85% of the responders appreciated online sessions happening during pandemic to avoid wastage of time but as high as 50% students were of the opinion that teachers could not maintain standard of teaching as in on campus session. Factors for this dis-satisfaction of students included issues like connectivity issues, gadgets of students as well as teachers, novelty to softwares to attend online class, and psychological issues like depression. So at the end 83% of students preferred on-campus sessions on on-line sessions. Conclusion: On the basis of findings of this study, it is recommended that we should continue activity of online teaching with improvement in resources and train our staff and students even in the absence of such emergency. Keywords: E-learning, Online learning, COVID pandemic, Learner’s perspective, Developing country, Medical education, Educational preparedness, satisfaction of learner,